2017
DOI: 10.1073/pnas.1701482114
|View full text |Cite
|
Sign up to set email alerts
|

Common general anesthetic propofol impairs kinesin processivity

Abstract: Propofol is the most widely used i.v. general anesthetic to induce and maintain anesthesia. It is now recognized that this small molecule influences ligand-gated channels, including the GABA A receptor and others. Specific propofol binding sites have been mapped using photoaffinity ligands and mutagenesis; however, their precise target interaction profiles fail to provide complete mechanistic underpinnings for the anesthetic state. These results suggest that propofol and other common anesthetics, such as etomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 71 publications
5
48
0
Order By: Relevance
“…It seems likely that these inhibitors will work in a similar way and recognize specific sequences in this region of the particular motor. A recent study of inhibition of kinesin-1 by the general anesthetic propofol showed that kinesins active in interphase are also susceptible to perturbation of their ATPase cycles by small-molecule binding; this could be explained through mechanisms related to disruption of subdomain rearrangements ( 68 ). Thus, our study of BTB-1 inhibition of Kif18A reinforces a common mechanism of allosteric kinesin inhibition through binding at the dynamic interface of subdomains within the kinesin motor domain, either on or off the MT ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that these inhibitors will work in a similar way and recognize specific sequences in this region of the particular motor. A recent study of inhibition of kinesin-1 by the general anesthetic propofol showed that kinesins active in interphase are also susceptible to perturbation of their ATPase cycles by small-molecule binding; this could be explained through mechanisms related to disruption of subdomain rearrangements ( 68 ). Thus, our study of BTB-1 inhibition of Kif18A reinforces a common mechanism of allosteric kinesin inhibition through binding at the dynamic interface of subdomains within the kinesin motor domain, either on or off the MT ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the commonly administered general anesthetic propofol ( Fig. 2 A ) at clinically relevant concentrations inhibits the processive movement of kinesin-1 KIF5B and kinesin-2 KIF3AB and KIF3AC ( 26 ). The single molecule results showed that the average distance these kinesins could step decreased 40–60% with EC 50 values <100 n m propofol with no effect on the velocity of movement.…”
Section: Introductionmentioning
confidence: 97%
“…These results indicate that propofol is not binding at the ATP-binding site or allosteric sites that modulate microtubule-activated ATP turnover. Rather, the results suggest that during a processive step on the microtubule, an allosteric binding site for propofol forms, propofol binds and disrupts the kinesin–microtubule interaction, and therefore results in kinesin detachment to end the processive run ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Should these tracks be decorated with bound anesthetic molecules, it is plausible that motor function and ultimately transport would be altered. In single-molecule experiments, where, instead of its usual cargo, kinesin is attached to a fluorescent bead and microtubules are immobilized on a substrate, it was noticed that clinically relevant concentrations of propofol reduced run length by half and had no effect on velocity 78 . In other words, the train goes just as fast but derails.…”
Section: Other Molecular Targets Of Propofolmentioning
confidence: 99%